2021
DOI: 10.1111/bjet.13118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual reality application on skill learning for optical‐fibre fusion splicing

Abstract: Virtual reality (VR) is a way of digitally simulating or replicating an environment (Meyer et al., 2019). The four fundamental elements of VR are three-dimensional multimedia, immersion, sense of presence and interactions between the virtual and real environments (Makransky et al., 2019;Radianti et al., 2020). From its application in entertainment in the 1960s to flight training purposes in the 1980s (Makransky et al., 2019;van Ginkela et al., 2019), VR has demonstrated favourable teaching effects and widespre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Some researchers have indicated that true immersive VR experiences can be provided by situating learners in a fully computer‐generated, surrounding, stereoscopic 3D environment that attempts to simulate some aspect of reality and, more importantly, can be navigated and interacted with (Schroeder, 2008; Sherman & Craig, 2003). However, several scholars have pointed out the benefits of using 360° videos or static environments that are not computer‐generated with computer software to stitch together the images into a sphere that surrounds the viewer, including the authentic levels of using real videos and images as well the economic and low‐tech considerations of developing the learning content (Chang, 2021; Cheng & Chen, 2016). Therefore, this study proposed a spherical video‐based virtual reality (SVVR)‐based professional training (SVVR‐PT) approach, combining VR and the attention, relevance, confidence and satisfaction (ARCS) model, to attract learners' interest and stimulate their curiosity in the professional training programme, and to increase the opportunities for experiencing and practising.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have indicated that true immersive VR experiences can be provided by situating learners in a fully computer‐generated, surrounding, stereoscopic 3D environment that attempts to simulate some aspect of reality and, more importantly, can be navigated and interacted with (Schroeder, 2008; Sherman & Craig, 2003). However, several scholars have pointed out the benefits of using 360° videos or static environments that are not computer‐generated with computer software to stitch together the images into a sphere that surrounds the viewer, including the authentic levels of using real videos and images as well the economic and low‐tech considerations of developing the learning content (Chang, 2021; Cheng & Chen, 2016). Therefore, this study proposed a spherical video‐based virtual reality (SVVR)‐based professional training (SVVR‐PT) approach, combining VR and the attention, relevance, confidence and satisfaction (ARCS) model, to attract learners' interest and stimulate their curiosity in the professional training programme, and to increase the opportunities for experiencing and practising.…”
Section: Introductionmentioning
confidence: 99%
“…While VR gained early approval and acceptance in the fields of engineering and the medical sciences, its use has spread to all disciplines (Vergara et al, 2021). Some findings show the positive impact of VR on student performance (Liu et al, 2020; Schott & Marshall, 2021; Tai et al, 2022) and practical skills (Chang, 2021; Morélot et al, 2021). Due to the ability to revisit training scenarios repeatedly, VR can also reduce training costs (Barteit et al, 2021).…”
Section: Introductionmentioning
confidence: 99%